Regulatory impact assessment in Sri Lanka the bridges that have to be crossed - Knight-John, Malathy; Jayasinghe, Shanta; Perumal, Andrew (2003)
This study was designed with the objective of gathering - so as to facilitate evaluation - the varied and often contradictory positions of regulation in Sri Lanka, both among the regulators themselves, and the perception of their actions among various stakeholders. By analyzing the functioning of the telecommunications regulatory agency and the proposed multisector utilities regulatory agency, it hopes to identify the actual regulatory practices in use and thereby offer long-term corrective measures, if any were needed. In terms of this analysis, the main point of reference was the Regulatory Impact Assessment (RIA) methodology developed in collaboration with our research partners at the Center on Regulation and Competition (CRC), Manchester. Furthermore, it is the view of the authors that this system, if applied to Sri Lanka, could greatly negate the multifarious problems that plague regulation: poor decisionmaking, and regulatory capture posing the worst threats. The findings of this study were not surprising in any way: regulatory processes are conducted in an ad hoc manner with little heed given to transparency and accountability, resulting in very few positive outcomes. Moreover, progress towards the establishment of a systematic process is slow and the adoption of a stringent (or any) impact assessment practice is being sidelined due to a perceived need to expedite the liberalization of the economy at all costs. The main recommendation of this study is that the only way forward, with an eye on progress towards a better era of regulation, is through the creation of awareness of the benefits of RIA among all stakeholders. It is hoped that a greater level of objectivity will gradually be infused into the regulatory processes in Sri Lanka once such a system is adopted.
Keywords: Information and Communications Commission of Sri Lanka (ICCSL); Liberalization (Finance) -- Sri Lanka; Privatization policies -- Sri Lanka; Public Utilities Commission of Sri Lanka; Regulatory impact assessment -- Sri Lanka; Regulatory policy -- Sri Lanka; Sri Lanka Institute of Development Administration; Sri Lanka Institute of Local Governance; Telecommunications Regulatory Commission of Sri Lanka